ANALISIS PERKERASAN LENTUR DI ATAS TANAH EKSPANSIF - Mukhlis Mukhlis; Yuhanis Yunus; Sofyan M. Saleh (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
The segmented road of Bireuen-Takengon has often damaged in apart of its pavement structure due to the area of flexible pavement structure taken place upon an expansive soil that leads to depreciation caused by the influence of changes in the water level. The aim of this research method was to analyze the characteristics of the base soil underlying the pavement and to analyze the flexible pavement structure in the widening of the road. The observed area was Sta.70+175 s/d Sta.74+925 which taken place in Bener Meriah regency, sub-district of Timang Gajah. The results of USCS clarification show that the road of basal soil is included in the MH and OH with a PI value of 25.42%, LL 64.25% with a potential level of development and activity belonging to the medium-high category and also having mineral types of Illite. From the analysis of KENPAVE software, the design of flexible pavement structures is based on data planning that has a maximum stress and deflection value, on the base soil, of 0.1814 kg/cm2 and 0.0585 cm respectively. Moreover, based on Job mix data the maximum value of stress and deflection is 0.2444 kg/cm2 and 0.0585 cm respectively in which both of two stress and deflections are within the allowable limit; which both of two stress and deflections are within the allowable limit; 7.8 kg/cm2 and 2.5 cm. The evaluation results of both data are feasible to be used as an improved design on the pavement as the pressure generated by the weight of the road pavement structure is 1.949 kg/cm2, while the swell pressure that occurs on subgrade is 1.805 kg/cm2. Hence, The flexible pavement structure on the road segment is still able to reduce the swell potential on expansive soil.